Pemakaian Modul Pembelajaran Sejarah di SMA N 6 Padang - Nanda Permana (Jurnal Pendidikan Sejarah, 2016)
Background of this research is the module who was made by the teachers of history at 6th high school. Module was purposed to make the student to be easier in their study. Module gives them something that teacher can’t do and it has something different than other sources. Learning by the module is a teacher history initiative, this can be seen from this school is the only one who uses this module. This research aims to know about the opinion of teachers and students about the effectiveness of the module in the learning process. Kind of this research was descriptive-qualitative. The data taken from two history teachers, sixteen students of class X1, 6 student of class X2 and sconehool leader. The data obtained using the techniques of observation, interviews and documentation. Validity of the data in this study were tested using data triangulation technique. Then the data were analyzed with data reduction, data presentation, and conclusion. The results showed that, the modules made by the subject teachers of history used by all students, so that modules made effective then teachers should refer to the theory proposed by M. Rogers Everret where modules have advantages, consistent, complexity, can be tested and observed. The fifth aspect presented by Rogers is already almost owned by modules made by the subject teachers of history.